Microfinance Consensus Guidelines : Guiding Principles on Regulation and Supervision of Microfinance - Christen, Robert Peck; Lyman, Timothy R.; Rosenberg, Richard (CGAP and World Bank, Washington, DC, 2014)
Many developing countries and countries with transitional economies are considering whether and how to regulate microfinance. These guiding principles are formulated for the regulation and supervision of microfinance. This document is divided into five sections. The first section of the paper discusses terminology and preliminary issues. The second section outlines areas of regulatory concern that do not call for "prudential" regulation. The next section discusses prudential treatment of microfinance and Microfinance Institutions (MFIs). The fourth section briefly looks at the challenges surrounding supervision, and the final section summarizes some key policy recommendations.